Changes in Visual Acuity and Keratometry Readings following Pterygium Excision: A Study in A Public Medical College Hospital - Rab, Jewell Ilias; Barna, -; Rahman Akanda, Md Ashiqur; Paul, Debabrata (Journal of National Institute of Ophthalmology, 2022)
Introduction: Pterygium is a degenerative, triangular wing shaped, fibro vascular connective tissue of bulbar conjunctiva towards and onto the cornea, leading to significant astigmatism. It is a common ophthalmic condition of tropical and sub-tropical country like Bangladesh where there is dry sunny hot dusty climate. Purpose: To find out the change in visual acuity and keratomety before and after pterygium excision and effect of different grades of pterygium on the final outcome. Methods: This prospective study was carried out from March 2021 to December 2021 at Ophthalmolgy Department, Sher-E-Bangla Medical College & Hospital, Barishal. Total 68 patients with different grades of pterygium were operated for pterygium excision with conjunctival autograft and were studied and analyzed. All the eyes underwent detailed ocular examination like visual acuity measured by Snellen’s chart; refractive astigmatism measured by automated keratometry and slit lamp biomicroscopy and fundus examination. Results: Pterygium is more common in males (61.76%) than females (38.23%) where 45.59% cases were in age group of 31-40 years followed by 33.82% in 41-50 years and rare (2.94%) in more than 60 years; so, 86.76% cases are in the age group of 31-60 years. Preoperatively mean±SD of K1 (Horizontal meridian) was 42.428±1.853 D and 3 month after the surgery it was 42.061±0.563 D. On the other hand mean±SD of K2 (vertical) readings before surgical excision were 44.185± 0.871 D and postoperatively after 3 months it was 42.691±0.384 D. Pre and post-operative BCVA in Grade I pterygium cases were 6/6-6/9 both pre & post -operatively. In patients of Grade II preoperative VA was 6/18-6/36 which was postoperatively 6/12-6/18; in Grade III pre and postoperative VA was 6/24-6/36 and 6/12-6/18 respectively. While in Grade IV pterygium VA were 6/36-6/60 preoperatively and 6/18-6/24 postoperatively. Conclusion: We conclude that, the greater the grade of pterygium the lesser is the outcome of visual acuity after surgery; the greater was the change in keratometry reading. It was inferred that, timely and appropriate surgery at Grade II & Grade III can result in not only a good visual outcome but also less complications. J. Natl. Inst. Ophthalmol. 2022; 5(2):25-30